Dilated cardiomyopathy mutations in thin-filament regulatory proteins reduce contractility, suppress systolic Ca²⁺, and activate NFAT and Akt signaling - Robinson, P; Sparrow, AJ; Patel, S; Malinowska, M; Reilly, SN; Zhang, YH; Casadei, B; Watkins, H; Redwood, C (American Physiological Society, 2020)
Dilated cardiomyopathy (DCM) is clinically characterized by dilated ventricular cavities and reduced ejection fraction, leading to heart failure and increased thromboembolic risk. Mutations in thin-filament regulatory proteins can cause DCM and have been shown in vitro to reduce contractility and myofilament Ca2+-affinity. In this work we have studied the functional consequences of mutations in cardiac troponin T (R131W), cardiac troponin I (K36Q) and α-tropomyosin (E40K) using adenovirally transduced isolated guinea pig left ventricular cardiomyocytes. We find significantly reduced fractional shortening with reduced systolic Ca2+. Contraction and Ca2+ reuptake times were slowed, which contrast with some findings in murine models of myofilament Ca2+ desensitization. We also observe increased sarcoplasmic reticulum (SR) Ca2+ load and smaller fractional SR Ca2+ release. This corresponds to a reduction in SR Ca2+-ATPase activity and increase in sodium-calcium exchanger activity. We also observe dephosphorylation and nuclear translocation of the nuclear factor of activated T cells (NFAT), with concordant RAC-α-serine/threonine protein kinase (Akt) phosphorylation but no change to extracellular signal‐regulated kinase activation in chronically paced cardiomyocytes expressing DCM mutations. These changes in Ca2+ handling and signaling are common to all three mutations, indicating an analogous pathway of disease pathogenesis in thin-filament sarcomeric DCM. Previous work has shown that changes to myofilament Ca2+ sensitivity caused by DCM mutations are qualitatively opposite from hypertrophic cardiomyopathy (HCM) mutations in the same genes. However, we find several common pathways such as increased relaxation times and NFAT activation that are also hallmarks of HCM. This suggests more complex intracellular signaling underpinning DCM, driven by the primary mutation.